Television Broadcast Media Adoption of Digital Platforms and Audience Engagement Within the Jalingo Metropolis - Apuke, Oberiri Destiny; Felix, David (Darul Yasin Al Sys, 2024)
This study investigated mainstream television adoption of digital platforms and audience engagement to determine the level of audience engagement, motivation for engagement, and challenges associated with engagement with TV stations on their digital platforms. The study focuses on Channels TV and the Nigeria Television Authority (NTA). A mixed research method was adopted, and the population of the study was viewers of Channels TV and NTA in the Jalingo metropolis. Data were collected from a valid sample of 331 respondents through a questionnaire and analyzed using descriptive statistical tools. The study found a moderate level of audience engagement on the digital platforms of the TV outlets. The study further revealed that the audience is motivated to engage with the stations via digital platforms based on their desire to stay updated and the convenience and interactivity offered by digital platforms. However, the study revealed that issues of slow loading times, low video streaming quality, high data consumption, and outdated content were the major challenges impeding audience engagement with Television outlets via the digital platform. The study recommends that TV stations should prioritize the production of high-quality content on their digital platforms and ensure regular updates of information and interactivity on their platforms.